The Relationship Between Adolescents' Knowledge and Attitudes on Reproductive Health and the Utilization of Information Media - Rahmawati, Lailatul; Kustin; Milla, Izatul (Journal of Nursing Periodic, 2025)
Introduction: Adolescence is a transitional phase from childhood before entering adulthood. During this period, significant changes occur in physical, cognitive, and psychosocial growth and development. Psychological changes also take place in adolescents, such as changes in intellectual capacity, emotional life, and social life. These changes can lead to internal conflicts in adolescents, often resulting in strange or awkward behaviors. If not properly managed, these can lead to juvenile delinquency, including risky sexual behaviors. Many problems may arise from neglecting reproductive health. One of the factors that affects adolescent reproductive health is the confusing information children and adolescents receive about the functions and processes of reproduction. This study aims to analyze the relationship between adolescents' knowledge and attitudes about reproductive health and their use of information media. Methods: This research is an analytical study with a cross-sectional design. A total of 38 respondents were selected using a simple random sampling technique. Data analysis was conducted using the Fisher Exact test. Results: The results showed a relationship between knowledge of reproductive health and the use of information media, with the Fisher Exact test yielding a p-value of 0.027, which is greater than α (0.05). Similarly, there was a relationship between attitudes toward reproductive health and the use of information media, with the Fisher Exact test also yielding a p-value of 0.027, which is greater than α (0.05). Conclusions: In conclusion, there is a relationship between knowledge and attitudes about reproductive health and the use of information media.